ChemInform Abstract: Octahedral‐Shaped Perovskite Nanocrystals and Their Visible‐Light Photocatalytic Activity. Issue 31 (5th August 2014) - Yin, Simin; Tian, He; Ren, Zhaohui; Wei, Xiao; Chao, Chunying; Pei, Jingyuan; Li, Xiang; Xu, Gang; Shen, Ge; Han, Gaorong
Abstract Octahedral perovskite PbTiO3 nanocrystals with well‐defined 111 facets enclosed are prepared via hydrothermal treatment of an alkaline TiO2 solution and Pb(NO3)2 in a 1:1.25 molar ratio using LiNO3 as an ionic surfactant (autoclave, 200 °C, 12 h).